PERTUMBUHAN HUKUM PIDANA DALAM MENGHADAPI PENINGKATAN KEJAHATAN - Rampadio, Hamdan (AKTUALITA, 2011)
The development of crime in various aspects is indicated by thedevelopment of the kinds of criminal model both in terms of qualityand quantity. Regulation of criminal law as one of the important efforts incombating crime and being a part of the growth of criminal law in facingthe development of crime. Moreover, political factors and criminal lawpolicies are also effecting the ability of criminal law in tackling crime.Keywords: crime, regulation of criminal law,criminal law policy.